(untitled) (Cultura Económica, 2019)
The author considers in his article the Chapter VI of the papal document, entitled “The development of people and technology”. The article sees human development as a part of a transcendent call which must avoid the self-sufficiency that endangers the search for ultimate meanings. Caritas in veritate claims that efficiency and utility should not be the only judgement criterion and should be integrated into the framework of a tradition of wisdom open to the question for true purpose.